RAILROAD ACCOUNTING UNDER THE NEW DEPRECIATION GUIDELINES AND INVESTMENT TAX CREDIT. - Dean, Joel; Harriss, C. Lowell (The Accounting Review, 1963)
Abstract The analysis in this article applies in general to the investment credit. This tax measure was introduced even more emphatically than the guidelines to stimulate investment. Accounting requirements, which would reduce the attractiveness or the apparent attractiveness of the credit, would run counter to public policy. Companies will get the investment credit if they qualify; it is not a matter of choice; in this respect the credit differs from the guidelines. From the point of view of the public interest, a part of the problem is whether one or another method of reporting would be more effective in demonstrating to management the benefits from the credit. If the tax savings had to be set off in tax deferral accounts the near-money gains of the investment credit might seem smaller and the stimulus to investment somewhat reduced. The tax advantage for a profitable railroad comes when the qualifying investment is made. Of course, complications will arise in some cases. There are contingencies, which can lead to the loss of some of the credit received on investments in prior years. And there will be carryovers of unused credits. The effect of a credit received in one year on the tax-worth of depreciation deductions in the future will present difficult, often insuperable, valuation problems.